Ratifikasi Asean Agreement On Electronic Commerce Oleh Indonesia - Indrawati Indrawati; Kartika Fitri Ampiranti (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This research examines the study of the ratification of the ASEAN Agreement on E-commerce by Indonesia. The research used in this research is a qualitative research which is described descriptively. Various sources were processed in this study such as books, research results, journals, and research articles. The results of this study indicate that in the current ICT era, e-commerce is a new way of conducting commercial activities, and is an important component in increasing economic growth and development around the world. For example, ASEAN, ICT, and e-commerce are recognized as important segments for regional integration. ASEAN is developing its legal framework to promote and facilitate ICT development and e-commerce growth in the region through the ASEAN Agreement on Electronic Commerce. On September 7, 2021, Indonesia has ratified the bill related to the ASEAN Agreement on Electronic Commerce to become a legal law in Indonesia. With the passing of the Draft Law into Law, the DPR and the government have formed a legal umbrella for cooperation in the intergovernmental electronic commerce sector in ASEAN to increase the value of trade in goods and services, increase the competitiveness of domestic business actors, and expand cooperation through the use of electronic commerce in ASEAN.